2018
DOI: 10.1016/j.jaerosci.2018.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Design and optimization of a compact low-cost optical particle sizer

Abstract: Direct measurements of time- and size-resolved particulate matter (PM) concentrations are of major importance in air quality studies and pollution monitoring. Low-cost, compact optical particle counters (OPCs), which provide accurate PM measurements independent of the particle complex index of refraction (CRI), can be useful in personal exposure monitoring and distributed sensor network studies applications. A methodology is presented for the optimization of the sensor design and operation parameter space aime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 41 publications
0
20
0
Order By: Relevance
“…From results in Figure 3b we see that the total particle sizing error of 1.5µm particle can exceed 1µm. Comparing to existing sizing error studies [4], the relative sizing error of position is shown to exceed the sizing error of an unknown complex refractive index of particles and therefore one of the biggest sources of error for the integrated optical particle sensor. Since the positional error is systematic, such sensor would have extremely poor sizing performance and would rather be limited to particle counting only.…”
Section: Lorentz-mie Scattering Simulationsmentioning
confidence: 63%
See 4 more Smart Citations
“…From results in Figure 3b we see that the total particle sizing error of 1.5µm particle can exceed 1µm. Comparing to existing sizing error studies [4], the relative sizing error of position is shown to exceed the sizing error of an unknown complex refractive index of particles and therefore one of the biggest sources of error for the integrated optical particle sensor. Since the positional error is systematic, such sensor would have extremely poor sizing performance and would rather be limited to particle counting only.…”
Section: Lorentz-mie Scattering Simulationsmentioning
confidence: 63%
“…It is therefore important to maintain ambient air quality at appropriate levels, from where an increased need for personal monitoring of airborne fine particles emerges. Recently, various integrated compact light-scattering optical particle counters have been reported for time-and size resolved measurement of the particles [2][3][4][5]. These designs often avoid the light collection optics on account of the overall sensor footprint and rather collect the light with the photodetector directly [4,6].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations